The role of implementation science training in global health: from the perspective of graduates of the field's first dedicated doctoral program. Issue 1 (1st December 2016) - Means, Arianna R.; Phillips, David E.; Lurton, Grégoire; Njoroge, Anne; Furere, Sabine M.; Liu, Rong; Hassan, Wisal M.; Dai, Xiaochen; Augusto, Orvalho; Cherutich, Peter; Ikilezi, Gloria; Soi, Caroline; et al.
Abstract : Bridging the 'know-do gap' is an enormous challenge for global health practitioners. They must be able to understand local health dynamics within the operational and social contexts that engender them, test and adjust approaches to implementation in collaboration with communities and stakeholders, interpret data to inform policy decisions, and design adaptive and resilient health systems at scale. These skills and methods have been formalized within the nascent field of Implementation Science (IS). As graduates of the world's first PhD program dedicated explicitly to IS, we have a unique perspective on the value of IS and the training, knowledge, and skills essential to bridging the 'know-do gap'. In this article, we describe the philosophy and curricula at the core of our program, outline the methods vital to IS in a global health context, and detail the role that we believe IS will increasingly play in global health practice. At this junction of enormous challenges and opportunities, we believe that IS offers the necessary tools for global health professionals to address complex problems in context and raises the bar of success for the global health programs of the future.